Undesirable social relations as risk factors for loneliness among 14-year-olds in the UK: Findings from the Millennium Cohort Study. (January 2022) - Yang, Keming; Petersen, Kimberly J.; Qualter, Pamela
In the current study, data collected from Wave 6 of the Millennium Cohort Study ( n = 11, 872), a nationally representative sample survey of youth aged 14 years in the UK, are used to examine the prevalence of loneliness among this age-group, investigate the feelings associated with the experience of loneliness among youth, explore the risk factors for loneliness among young people, and learn how they coped with loneliness. Given recent findings that youth are vulnerable to loneliness, the study assesses the prevalence of loneliness among adolescents across some important sociodemographic characteristics, such as nation of residence, gender, and ethnicity. We also identify the kinds of social experiences that accompany loneliness during adolescence, exploring friendship, relations with parents, social support, and bullying. Our key finding is that, in addition to the absence of desired social relationships, which has been typically identified as the ultimate source of loneliness, the presence of undesirable and even harmful social relationships is a major source of loneliness. This study uniquely brings together psychological and sociological perspectives to understand the experience of youth loneliness.